Espacio escolar y tribus urbanas : el caso de la Institución Educativa San José Obrero en el corregimiento San Antonio de Prado (2012)
ABSTRACT: This ethnography intends to study the space appropriation by the different urban tribes that coexist in San Jose Obrero School. By observing that appropriation is possible to recognize some of the rituals, beliefs, costumes, desires and imaginaries; as well as corporal expressions that show different usages in the scholar life, related to space membership. These behaviors are seen in different places, such as playgrounds, hallways, sport areas and the physical education class, through pictures, interviews and institutional journals. This research goes inside the ethno-corporal problems and students disposition in school.